Community Resilience to Disaster and Climate Change to Support Sustainable Development In and After The Covid-19 Pandemic - Purba, Anggiat; Widana, I Dewa Ketut Kerta; Hadi Sumantri, Siswo; Kurniadi, Anwar; Mayori, Ersha (Technium Social Sciences Journal, 2022)
Countries all over the world are busy looking for the best way to reduce global warming caused by climate change. Based on the report from the World Economic Forum in 2021, the probability of the highest levels in the next ten years are extreme weather, climate control failures, and environmental damage is increasing due to human actions or anthropogenic factors. Global warming and climate change will increasingly be felt by life on earth. The phenomena of Elnina, laminae, cyclonic storms, floods, landslides, droughts, tidal waves and tidal waves, rising sea levels cause tidal waves that are closely related to global warming and climate change. In the midst of the world facing climate change, the world community is also facing disasters due to the Covid-19 pandemic, which has caused many human casualties, and a wide impact on social, political and economic life. This article discusses community resilience to climate change to support sustainable development during and after the Covid-19 pandemic. This study uses a qualitative approach with a descriptive method. Qualitative methods rely on text and visual data, while data collection techniques are carried out through observation, interviews, literature studies, and focus group discussions (FGD) through zoom meetings. The result is: the world community has paid serious attention and efforts to deal with and adapt to climate change and minimize its impacts. Many risk reduction efforts have been carried out, starting at the local, national, regional and even global levels, including efforts to overcome the Covid-19 pandemic with the New-normal model of life and increasing vaccination achievements for herd immunity. These efforts require the support of all parties, starting from increasing individual awareness to the international level. Overall, the effort to reduce disaster risk is to build community resilience against all forms of disaster risk threats and sustainable development. Resilience in the face of disasters will save people and invest in the welfare of humanity at large.